Preoperative imaging of glioblastoma patients using hyperpolarized 13C pyruvate: Potential role in clinical decision making. Issue 1 (28th June 2021) - Chen, Jun; Patel, Toral R; Pinho, Marco C; Choi, Changho; Harrison, Crystal E; Baxter, Jeannie D; Derner, Kelley; Pena, Salvador; Liticker, Jeff; Raza, Jaffar; Hall, Ronald G; Reed, Galen D; et al.
Abstract: Background: Glioblastoma remains incurable despite treatment with surgery, radiation therapy, and cytotoxic chemotherapy, prompting the search for a metabolic pathway unique to glioblastoma cells. 13 C MR spectroscopic imaging with hyperpolarized pyruvate can demonstrate alterations in pyruvate metabolism in these tumors. Methods: Three patients with diagnostic MRI suggestive of a glioblastoma were scanned at 3 T 1–2 days prior to tumor resection using a 13 C/ 1 H dual-frequency RF coil and a 13 C/ 1 H-integrated MR protocol, which consists of a series of 1 H MR sequences (T2 FLAIR, arterial spin labeling and contrast-enhanced [CE] T1 ) and 13 C spectroscopic imaging with hyperpolarized [1- 13 C]pyruvate. Dynamic spiral chemical shift imaging was used for 13 C data acquisition. Surgical navigation was used to correlate the locations of tissue samples submitted for histology with the changes seen on the diagnostic MR scans and the 13 C spectroscopic images. Results: Each tumor was histologically confirmed to be a WHO grade IV glioblastoma with isocitrate dehydrogenase wild type. Total hyperpolarized 13 C signals detected near the tumor mass reflected altered tissue perfusion near the tumor. For each tumor, a hyperintense [1- 13 C]lactate signal was detected both within CE and T2 -FLAIR regions on the 1 H diagnostic images ( P = .008). [ 13 C]bicarbonate signal was maintained or decreased in the lesion but the observation was not significant ( P = .3). Conclusions: Prior to surgical resection, 13 C MR spectroscopic imaging with hyperpolarized pyruvate reveals increased lactate production in regions of histologically confirmed glioblastoma.